SYNTHESIS AND PROPERTIES OF THE SYSTEMS Eu1-XPrXBa2Cu4OY (0£X£0,5) AND Eu1-XTbXBa2Cu4OY (0£X£0,5): UDC 546.431'65'56 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2008)
The samples Eu1-xPrxBa2Cu3Oy і Eu1-xTbxBa2Cu4Oy (0£x£0,5) were synthesized by ceramic technique. The structural parameters electrophysical properties and oxygen content depend on their composition were study. The electrophysical properties depend on the type of atom REE was investigate.
Keywords: -